PERGUMULAN KEBATINAN JAWA MEMAKNAI KEHADIRAN YESUS KRISTUS - Antonius Kurnia Andrianto (P3TK, Sanata Dharma University, 2016)
The local Church of the Archdiocese of Semarang (KAS) grows and develops in the Javanese culture. Before their conversion to Catholicism, many local Catholics held Kebatinan, a Javanese religious tradition, as their religion. Even after their conversion, some of them continue to practice some forms of the Javanese mysticism. In order to give a space for Catholics who are practicing such a mysticism, a forum called